FACTORS INFLUENCING HEALTH WORKERS' PERFORMANCE IN PUBLIC HEALTH FACILITIES IN THE DEVOLVED SYSTEM OF GOVERNMENT: A CASE OF EMBAKASI EAST SUB-COUNTY, NAIROBI COUNTY - Atieno, Theresepaul Odundo; Echakan, Mr. Daniel Esimit; Osuga, Mr. Ben Onyango (Global Journal of Health Sciences, 2018)
Purpose The main objective of carrying out this research was to evaluate the factors that affect the performance of health workers in public health facilities within the County system in Kenya. Methodology: A descriptive study approach was used.The sample size was all the six public health facilities in Embakasi East Sub-County. The study further purposively sampled ten (10) key informants from each of the public health care facilities and collected data from this sample using self-administered questionnaires as the main data collection tool. Statistical data analysis was carried out using SPSS version17.0 and data was presented in graphs, tables and discussions. Results: The study found that training, staff recognition and staff participation are important aspects for improving the capacity and motivation of health care workers. The study also identified commendable efforts in training of health workers as a way to improve competence. Unique contribution to theory, practice and policy: In achieving improvement of these components the County Government system can be able to improve the performance of the health workers and assist in strengthening the health care service provision in the country. Public health officials should also continuously conduct organizational systems studies in order to identify weaknesses and loopholes as well as put measures in place to seal those loopholes and subsequently enhance performance, especially in reference to resource allocation.Public health facilities must also strive to build a strong ethical culture through proper selection systems, leadership by example and effective performance management systems to ensure and enhance performance